Youth’s self-construction in the context of residential care: The looking-glass self within the youth-caregiver relationship - Silva, C. S. (2022)
Youth in residential care typically struggle to construct a positive sense of self, given their often highly adverse life experiences. However, the processes that explain youth’s self-representations process in residential care have not been systematically analyzed. Based on the symbolic interactionism theory, this study addressed this gap in the literature by testing the Looking Glass Self Hypothesis (LGSH) in this development context within the relationship between youth and their main residential caregiver. Participants were 755 youth from 71 residential care units in Portugal, 12-25 years old, and their respective main caregiver (N = 300). Through a multi-mediator model, we examined whether caregivers’ actual appraisals of the youth in care were associated with youth’s self-representations via caregivers’ reflected appraisals (i.e., youth’s perceptions of their main caregiver’ appraisals of them). Results supported the LGSH in the context of youth-caregiver relationships in residential care, emphasizing the important role of residential caregivers in youth’s self-construction process.